2015
DOI: 10.15376/biores.10.1.1224-1244
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Hardwood Sawmill Log Procurement Practices

Abstract: U.S. hardwood sawmill log procurement practices are evolving because of the recent economic recession, market and supply chain shifts, and changing landowner objectives, among other factors. The objective of this study was to characterize the log procurement practices of hardwood sawmills and to characterize the role that log brokers play in supplying the sawmill industry with raw material. To meet this objective, a mail survey on hardwood log procurement practices in the U.S. hardwood sawmill industry was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Although this could be true for some firms, anecdotal reports suggest that the vast majority of logging businesses in Arkansas operate as at-will loggers who maintain free agreements with the mills. Relatedly, Andersch et al (2015) also found that sawmills in the southern states procure more wood from gatewood loggers than in any other states, meaning that logs are hauled to sawmills primarily by independent loggers and are not preordered or ordered under a contract. Lastly, it is possible that there were fewer mill quotas given that 50% of the loggers decreased supply, allowing the other 31.6% of loggers to increase their production to fill the gap in the mills' demand.…”
Section: Resultsmentioning
confidence: 96%
“…Although this could be true for some firms, anecdotal reports suggest that the vast majority of logging businesses in Arkansas operate as at-will loggers who maintain free agreements with the mills. Relatedly, Andersch et al (2015) also found that sawmills in the southern states procure more wood from gatewood loggers than in any other states, meaning that logs are hauled to sawmills primarily by independent loggers and are not preordered or ordered under a contract. Lastly, it is possible that there were fewer mill quotas given that 50% of the loggers decreased supply, allowing the other 31.6% of loggers to increase their production to fill the gap in the mills' demand.…”
Section: Resultsmentioning
confidence: 96%